Analysis of the content of the book of biology for the first year in middle school in the light of the value dimension - Sahed, Fatiha (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2022)
The present study aimed at finding the availability of the value dimension in the book’s content of biology of the first year in middle school. To achieve this objective, the study used the analytical descriptive method, and it used a questionnaire consisted of 37 items for the measurement that was applied to the sample (the book’s content of biology of the first year in middle school). The results of the study were as following: The components of the value dimension are available in the content of the book in varying proportions. The emotional component achieved the lowest percentage, estimated at 18.18%, while the cognitive component ranked first with a rate of 50.41%, and the behavioral component achieved 31.40%. From this, we conclude that the book under analysis focused on the cognitive component to a greater degree than the behavioral component, and less on the emotional component. The study also came up with recommendations, includingm - The need to carry out studies and research in some detail on educational and social values in the content of various textbooks and in various subjects and methods of development -The Ministry should be interested in highlighting the values in textbooks. - Conduct comparative analytical studies between the contents of various textbooks in the light of the value dimension. - Conduct studies that address the impact of variables such as educational qualification, sex and others on various value dimensions such as cognitive, emotional and social values in specific age groups or elite groups.